Progression of clinical tuberculosis is associated with a Th2 immune response signature in combination with elevated levels of SOCS3 - Ashenafi, Senait (Clinical immunology (Orlando, Fla.), 2014)
Copyright © 2014. Published by Elsevier Inc.